The Impact of Model Courts on the Criminal Justice System of Khyber Pakhtunkhwa: A Case Study Based on Statistical Evaluation (Journal of Social Sciences Review, 2023)
The provision of inexpensive and expeditious justice is one of the constitutional responsibilities of the state, which is fulfilled through the instrument of the judiciary. In pursuance of the Expeditious Justice Initiative, the government of Khyber Pakhtunkhwa (hereinafter KP) established Model Courts in the province in 2019 with the purpose of introducing a time-bound criminal trial regime. The study in hand intends to evaluate the impact of Model Courts on reducing the pendency of criminal cases in KP. To achieve this objective, a questionnaire-based survey was designed, and data was collected from legal professionals as well as litigants. The study findings indicated that both legal professionals and litigants are satisfied with the establishment of the Model Courts and their functions, helping to adjudicate and dispose of the cases in efficient ways in the province. The study suggests that in order to evaluate the efficiency of statistical data regarding the outcome of the Model Courts in terms of its decisions, pendency, rate of conviction and acquittal and the ratio of reversal of its decisions on appeal, it is required to be rigorously analysed. The Model Courts have been used as a case study to bring about some positive changes in the contemporary criminal justice system of the province.
Keywords: Expeditious Justice; Model; Courts; Criminal Justice System; Speedy Trial; Rate of Conviction and Acquittal